AM I WHO I SAY I AM? THE ILLUSION OF CHOICE: BIOMETRIC IDENTIFICATION IN HEALTHCARE - Banville, Morgan Catherine (East Carolina University, 2023)
Grounded in surveillance studies and technical communication, this study defines biometric identification technologies as personal identifiers of the body, focusing specifically on how neonatal nurses use and perceive such technologies within the context of the United States healthcare system. As biometric identification and authentication becomes more commonplace within various sectors such as healthcare and medical-adjacent, it is crucial for technical communicators to return to the origins of biometric implementation to inform current interventions, and to question the reasons behind the urgency of implementing such technologies for efficiency, security, and compliance. Drawing from a corpus of communication materials from biometric companies, questionnaires, and ten interviews with neonatal nurses, this study explores the justification of implementing biometric technologies, including how biometric technologies are defined. Data analysis was conducted using interlocking surveillance, a framework that addresses sites of surveillance and their levels of awareness, advocacy, and transparency of normalized surveillant practices. This study contributes to understandings and perceptions that neonatal nurses have of biometric technologies in healthcare and extends far past the scope of privacy. Even so, privacy in this study is situated as both a tradeoff and illusion of choice: you can change your password, but you can't change your fingerprint. Because the U.S. has a preoccupation with security and surveillance technologies, this study can better inform technical communicators how to intervene in and implement decision-making practices. In particular, this study argues that neonatal nurses are technical communicators: they communicate and negotiate specialized information. The findings contribute to redefining what it means to be a technical communicator, re-rhetoricizing how technical communication is represented in the medical sector. Further takeaways from the study influence future coalitional work, questioning and revising normalized surveillance including ethics of biometric use, and localization of community input and participatory approaches for design of and intervention in communication materials.
Keywords: rhetoric; surveillance; feminism; neonatal nurse; Communication in medicine; Communication of technical information; Biometric identification; Neonatal nursing